An Analysis and Critique of the Translation of Al-Sharia Al-Arabiya with a Contrastive Criticism Approach to the Translation - Aliasghar Shahbazi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Al-Sharia Al-Arabiya, a book written by Adonis, is one of his works dealing with critique, published almost thirty years ago. Despite its small size, the book encompasses integrated information about the nature of Arabic poetry and its evolution through history. The author meticulously explores Arabic poetry and discusses its foundations from the perspective of ancient critics and orators. The four chapters of the book include subjects on origins of Arabic poetry, identity of rhythm and music of poetry, analysis of aesthetic issues and their connection with Qur'anic research, and struggle between tradition and modernity. The Persian version of the book, published under the title ‘Boutigha-ye Arabi’, is one of the most recent works by Adonis translated into Persian. The book is translated by Amir Abu Sassani and Omid Pourhassan by Amir Kabir Publications in 2018. The analysis of the translation of the book shows that despite some grammatical errors and inaccuracies in choosing equivalents, the translators have provided a proper translation, transmitting the message and the content fluently and expressively. Adding diacritical marks to the Quranic verses as well as lines and words in the poems and including a list of sources and indexes in the final part of the translation are the advantages of the book. However, with respect to the translation, inconsistency in using equivalents, collocational clashes, and improper omissions at the word level are some of the weak points.